Digital Signal Processing in Coherent Optical Radio Over Fiber Systems - Nabavi, Neda (Université d'Ottawa / University of Ottawa, 2017)
Coherent communication systems became practical with the advent of integrated electronic circuits capable of supporting Digital Signal Processing (DSP) at speeds compatible with line rates. Much of the complexity and expense of the functions required in a coherent receiver to compensate for optical channel uncertainties and impairments could be transferred to DSP algorithms. The aim of the research presented in this thesis is to develop radical breakthrough DSP algorithms and design new architectures for the digital coherent optical receiver within the RF-Cité system and optical fiber network supported distributed millimeter wave wireless antenna system. The model of an optical channel is fundamental for understanding phase and polarization drift, chromatic dispersion, polarization mode dispersion and other drawbacks of the fiber optic systems in order for the signal processing algorithm to compensate these effects. In this thesis firstly an evaluation of the optical channel model that accurately describes the single mode fiber as a coherent transmission medium is reviewed through analytical, numerical and experimental analysis. Secondly, an original approach to the design of a digital coherent optical receiver is proposed which can adapt to random time-varying state of polarization (SOP) for both the local oscillator and signal. To address the problem, two different methods of polarization diverse recovery of the modulation with carrier phase estimation and elimination of sign ambiguity are performed and verified by numerical simulations. The results show the accurate recovery of the modulation and error-free constellation demodulation. Furthermore, inspired by former investigations, the theoretical analysis of a novel microwave photonic integrated circuit (MPIC) implementations of various building blocks used within the RF-Cité architecture is presented. The application of the proposed circuit in RoF systems is demonstrated by computer simulations using the Virtual Photonics Inc. software and OptiSuite packages. The performance of the proposed MPIC in a RoF system is assessed through advance modulation format techniques that have been employed in many wireless communication standards owing to their high spectral efficiency. In the DSP module, delay compensation is applied to synchronize the received signal, and the system performance is evaluated by measuring the error vector magnitude of the received signal using single-mode fiber. This scheme removes the temperature control requirement; an undesirable feature in terms of energy consumption considerations. Also, a modified polarization demultiplexing algorithm is employed to classify the input polarizations that transmit two independent channels that are mixed randomly as the light is propagating in the optical fiber. This novel technique enables blind algorithms to accurately track polarization channel alignment, through achieving accurate polarization de-multiplexing obtained by numerical simulations and experiments.
Keywords: Coherent communication systems; Digital Signal Processing